Applications of Environmental Chemistry: A Practical Guide for Environmental Professionals - Weiner, Eugene R (CRC Press, 2009)
Up until the 1950s, waste disposal meant discharging it to the nearest river, burning it up or shipping it out to sea. Now we are paying the price. Current disposal and cleanup regulations have a different focus: correcting the problems caused by earlier misguided attitudes and maintaining a non-degrading environment. State and Federal clean air and water acts have created the need to identify and measure chemical components that affect the quality of surface and ground waters and the soils through which they flow.